Incidental Findings of Asymptomatic Fungal Infection - Nisha Manila; Madhu Nair; Hui Liang (Case Reports in Dentistry)
Fungal sinusitis of the paranasal sinuses is a rare infection in healthy individuals but is relatively common in immunocompromised patients. It is often misdiagnosed and frequently a severe disease, as a few forms of it are linked with a higher mortality rate. Effective handling necessitates a speedy analysis and often counts on radiological findings. On cone-beam computed tomography (CBCT) analysis, a bulky polypoid-shaped lesion with a density close to that of soft tissue in CBCT was visualized in the right ethmoid and sphenoid sinuses. There was a significant expansion of the borders of the right ethmoid sinus, and discontinuity or perforation of the sphenoid sinus floor was suspected from CBCT images. Non-contrasted multi-detector computed tomography (MDCT) exhibited opacification and extension of the lesion into the majority of sinuses with dense inspissated materials in the center, which resembled radiographic features of invasive fungal sinusitis. Computed tomography (CT) scan of the maxillofacial region, specifically paranasal sinuses, plays a considerable role in diagnosing fungal sinusitis. In a majority of cases, fungal sinusitis is noticed and diagnosed in immunocompromised patients. However, it is also seen in healthy patients in very rare circumstances, similar to the patient in this report. If the patient is treated rapidly, the prognosis is fair. We present a case of fungal sinusitis in an otherwise healthy young male patient to increase awareness among dental professionals.